Diabetes Mellitus in Multitransfused Thalassaemia Patients at Sir Ganga Ram Hospital, Lahore (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine diabetes mellitus in multitransfused thalassaemia patients and its relationship with iron overload at Sir Ganga Ram Hospital, Lahore. Method: A cross-sectional study was conducted among thalassaemia patients, at the Thalassaemia Centre, Paediatric Department, Sir Ganga Ram Hospital, Lahore. A structured questionnaire was used to collect information. The children included in the study were more than ten years of age and had multiple blood transfusions . All patients underwent a standardized glucose tolerance test (GTT). SPSS 17.0 was used for data entry and analysis. Results: A total of 107 thalassaemia patients participated in the study, 65 were males and 42 were females with age ranges of 10 – 30yrs(mean 15yrs). and the average BMI was 16. The mean time of diagnosis was 1.32yrs. The average age of having first blood transfusion was 3yrs. Iron chelation was started at an average of 7.58yrs; where as 95.3% of patients were using both iron chelation along with regular blood transfusions. The mean value for serum ferritin was 5671ng/ml and average pre-transfusion haemoglobin was 7.48gm. There were 4 cases of diabetes mellitus; out of which 3 had a significant family history of the disease. Nine (8.4%) of cases had an impaired glucose tolerance test. There was a significant association with fasting blood sugar , 2 hour GTT readings and serum ferritin levels (Fisher's Exact Test p-value of 0.045 and 0.024 respectively). Conclusion: The children with higher levels of ferritin were at a greater risk of developing endocrine dysfunction of the pancreas but family history of diabetes posed a greater risk of overt diabetes with elevated levels of ferritin. It is therefore recommended that iron chelation therapy be initiated earlier and especially in those having a strong family history of diabetes. Periodic screening for impaired glucose tolerance can help to identify and initiate timely appropriate interventions.